Passivity‐based control of MMC‐based active power filter under non‐ideal conditions. (1st December 2019) - Wang, Yujiao; Cheng, Qiming; Cheng, Yinman
Summary: To improve the voltage withstand level and maintain a high effective switching frequency of conventional active power filter, modular multilevel converter (MMC) with a high number of voltage levels is employed in shunt active power filter recent years, but few articles study this topology from the control strategy applicable to various non‐ideal states. This paper proposes a passivity‐based control (PBC) scheme for MMC‐based shunt active power filter (MMC‐SAPF) with independent positive‐ and negative‐sequence components, and the proper control laws have been defined based on the PBC method, which can also be applied to the non‐ideal state. The passivity of MMC‐SAPF and stability analysis are proved, and damping injection idea is used to design corresponding controllers with high dynamic performance. Besides, the overall control scheme is also based on circulation current suppressing controllers, submodule capacitor voltage controllers, and a harmonics detection section that can choose compensation signals flexibly according to the capacity of active power filter and is applicable in non‐ideal states, as well as ideal state, which can improve the comprehensive performance of this system. By comparing PBC with traditional PI control under ideal state and various non‐ideal operating states, the effectiveness and superiority of proposed strategy were validated by simulation and downscaled experiments.